2017
DOI: 10.1126/science.aah5043
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of intratumor bacteria in mediating tumor resistance to the chemotherapeutic drug gemcitabine

Abstract: Growing evidence suggests that microbes can influence the efficacy of cancer therapies. By studying colon cancer models, we found that bacteria can metabolize the chemotherapeutic drug gemcitabine (2′,2′-difluorodeoxycytidine) into its inactive form, 2′,2′-difluorodeoxyuridine. Metabolism was dependent on the expression of a long isoform of the bacterial enzyme cytidine deaminase (CDDL), seen primarily in Gammaproteobacteria. In a colon cancer mouse model, gemcitabine resistance was induced by intra-tumor Gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
1,256
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,246 publications
(1,306 citation statements)
references
References 29 publications
44
1,256
2
4
Order By: Relevance
“…The phenomenon that other cells than tumour cells, or even microbes inactivate or scavenge antineoplastic drugs is indeed compelling. A recent study has shown that intratumoural bacteria may significantly add to gemcitabine resistance in PDA 56. In this study, the authors compared the growth kinetics between tumours established from mycoplasma-positive and mycoplasma-negative tumour cells following gemcitabine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon that other cells than tumour cells, or even microbes inactivate or scavenge antineoplastic drugs is indeed compelling. A recent study has shown that intratumoural bacteria may significantly add to gemcitabine resistance in PDA 56. In this study, the authors compared the growth kinetics between tumours established from mycoplasma-positive and mycoplasma-negative tumour cells following gemcitabine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Strong links have also been reported for Salmonella typhi causing gall bladder cancer, Mycoplasma resulting in ovarian and lung cancer and many more [3]. A recent article in the journal Science demonstrated that the presence of bacteria inside tumor have also the potential to create resistance against cancer therapy due to their inherent capability of cleaving chemotherapeutics into inactive metabolites [5]. In this way, specific links between infectious pathogens and cancer can greatly impact the design of therapy.…”
Section: Historical Perspectivementioning
confidence: 94%
“…However, microbial metabolism is not always beneficial for the host. Writing in Science, Geller et al 4 report that bacteria within a tumour can metabolize an anticancer drug into an inactive form and thereby render it ineffective.…”
Section: H R I St I a N J O B I Nmentioning
confidence: 99%